Coplanar wave guide fed fork shaped frequency reconfigurable antenna for LTE, WI-FI and WLAN applications - Siva Prasad, B; Mallikarjuna Rao, P; T P Madhav, B (International Journal of Engineering and Technology, 2017)
A coplanar wave guide fed fork shaped antenna is designed with reconfigurability for switching between the application bands of LTE, Wi-Fi and WLAN. A novel closed hut shaped ground plane structure is used in the construction of the antenna model for good impedance matching with the feed line. The basic structure of the antenna model is working in the UWB range from 3.1 to 10.6 GHz. The adjacent strips of the monopole consisting of the slots for the placement of PIN diodes. The switching operation of the diodes providing frequency reconfigurability nature in the antenna between LTE (2.1-2.2 GHz), Wi-Fi (2.4 to 2.7 GHz) and WLAN (5.6-5.8 GHz) bands. Antenna is providing peak realized gain of 4.5 dB and efficiency more than 70% in the operating bands. The prototyped antenna is providing excellent measurement results in correlation with simulation results obtained from CST Microwave Studio.